Exploring fish communities in the mud volcano polluted river using environmental DNA metabarcoding - Firli Rahmah Primula Dewi; Hyun-Woo Kim; Ah Ran Kim; Soo Rin Lee; Amy Yee-Hui Then; Mochammad Zamroni; Flandrianto Sih Palimirmo; Henny Trie Wahyuni; Muhammad Hilman Fu'adil Amin (Environmental Advances, 2024)
In ecosystems subjected to environmental disturbances such as mud volcanoes, understanding the dynamics of fish communities is essential for ecological assessment and conservation. This study employs environmental DNA (eDNA) metabarcoding for the first time to explore fish communities within a challenging and unique environment—a mud volcano-polluted river. High-throughput sequencing was utilized to assess alpha and beta diversity, revealing distinct patterns in fish community composition in response to mud discharge activity. The results indicate that affected sites exhibit remarkably different communities during active and inactive mud discharge, with the impact extending downstream to the river mouth. Notably, the application of eDNA metabarcoding identified a vulnerable species, Rasbora lateristriata, emphasizing its utility in detecting high-risk species. Despite challenges in species identification and reference databases, the use of longer 16S rRNA fragments offered enhanced taxonomic resolution and interspecific sequence variation. This approach showcases the potential of eDNA metabarcoding in assessing fish diversity and community dynamics in polluted aquatic ecosystems, emphasizing its significance in biodiversity surveys and ecological monitoring. The study underscores the value of eDNA metabarcoding as an efficient and comprehensive tool for studying freshwater ecosystems and highlights the need for expanding reference databases to address genetic coverage gaps, particularly in less-studied environments.